Exploring Ideational Meaning in two Extracts from Ngugi Wa Thiongo’s A Meeting In The Dark - DADJO, Servais Dieu-Donné Yédia (My University, 2021)
This research work focuses on the study of ideational meaning in Ngugi Wa Thiongo’s A Meeting in the Dark. It aims to analyse linguistic features which connote experiential meaning so as to provide a new interpretation of this short story. Both quantitative and qualitative research methods have been used to carry out this work. The findings reveal the predominance of material processes in both extracts indicating that concrete and tangible actions have been performed by different characters namely John, Stanley and Susana. The study also shows that mental processes have been used to describe John’s fear of his father a converted man who establishes with strict laws of Christianity within his family in order to protect his son John against all evil influences. The exploration of the ideational meaning has helped contend that the deep message conveyed through the selected short story concerns Christianity and its impacts on African family lives. In other words, the short story has dealt with the various transformations that occurred in Africa in general and in African family lives with the arrival of Christian Missionaries in particular.
Keywords: Systemic Functional Linguistics; Transitivity analysis; ideational meaning; linguistic features.